Developing the Dynamic of Job Creation Augmented Model for Malaysian Manufacturing Sectors - Maamor, Selamah Binti; Samsi, Aznita; Samsuddin, Siti Nur Fatihah; Abdullah, Norehan; Abdullah, Hussin; Nayan, Sabri (International Journal of Supply Chain Management, 2019)
ABSTRACT The aim of this paper is to construct an Augmented Dynamic Model of Job Creation for Malaysian Manufacturing Sector. The previous studies on job creation model focus on the static model where the job creation influenced by real wages, real output, assets, expenditure of research and development (R&D), lag of R&D, export and foreign labour. However, the aggregate rate of unemployment in Malaysia could not explain the dynamic of labour market. The dynamic of labour market can be explained more precisely through the formula of job flows (including job creation and job destruction). Therefore, in this study, the augmented dynamic model of job creation constructed by added several variables including interaction variables. The augmented dynamic model of job creation is developed by using GMM model based on data 2005 to 2015 for Malaysian manufacturing sector. The augmented model of job creation is expected to be effective and informative guide policy maker to face unemployment rate especially Malaysia. This augmented model can portray a real situation of labour market and help the government as well as policy maker to plan of Malaysian economics in the future.